2007
DOI: 10.1021/jp073677i
|View full text |Cite
|
Sign up to set email alerts
|

Strong Brønsted Acidity in Amorphous Silica−Aluminas

Abstract: Monomolecular cracking of propane was used to investigate the activity of the Brønsted acid sites in amorphous silica−aluminas with three different Si/Al ratios. The reaction rates increased with increasing aluminum content, but the apparent activation energies were identical. In comparison to zeolite ZSM5, the ASA catalysts showed much lower activity, both per weight and per total aluminum content. However, after correcting for the heat of adsorption, the intrinsic activation energies of ASA and H-ZSM5 were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
135
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(156 citation statements)
references
References 32 publications
17
135
4
Order By: Relevance
“…This may be because of the decrease of Lewis acidity led to the low degree of Diels-Alder cyclization reactions as discussed below. In addition, many works showed that the catalytic dehydrogenation of alkanes like propane and butane to form the gaseous olefins might occur on the Brønsted acid sites [49][50][51]. These results indicated that the formation of olefins strong depends on the Brønsted acid density.…”
Section: Catalytic Conversion Of Soybean Oilmentioning
confidence: 99%
“…This may be because of the decrease of Lewis acidity led to the low degree of Diels-Alder cyclization reactions as discussed below. In addition, many works showed that the catalytic dehydrogenation of alkanes like propane and butane to form the gaseous olefins might occur on the Brønsted acid sites [49][50][51]. These results indicated that the formation of olefins strong depends on the Brønsted acid density.…”
Section: Catalytic Conversion Of Soybean Oilmentioning
confidence: 99%
“…It is classically well known that zeolite has the much higher activity and selectivity for gasoline in the catalytic cracking of heavy hydrocarbons compared with ASA [30]. Further, it was also reported in more recent literature that the catalytic performance for hydrocracking of n-heptane over USY [34] or propane cracking over ZSM-5 [35] was much higher than that for ASA. Although BrØnsted acid sites in ASA might have an intrinsic acidity close to that of zeolites, it was pointed out that the much lower activity for silica-aluminas was due to their very low acid site density [34].…”
mentioning
confidence: 99%
“…Zeolite-like bridging SiÀ(OH)ÀAl groups are sometimes invoked, [8,9] but are questioned by several other authors. [10,11] Silanols bonded to low-coordinated aluminum atoms by a SiÀOÀAl bridge have been proposed as most acidic Brønsted sites on ASA surfaces, depending on the number and coordination of aluminum atoms.…”
mentioning
confidence: 99%